Which one affect the other, Recurrent Pregnancy Loss or Serum Level of E?cadherin and c-MycBP - Zena Abdul-Ameer Mahdi; Nadia M. Al-Hilli; Maha F. Smaism (Institute of Medico-legal Publications Pvt Ltd, 2021)
Recurrent pregnancy loss (RPL) is a foremost life event and a common pregnancy complication, whichdefined as losses of two or more pregnancies before 20 weeks of gestation. It affects approximately 1% -2% of couples trying to have children. To evaluate the potential role of cellular myelocytomatosis bindingprotein (c-MycBP) and epithelial cadherin (E-cad) serum level as biomarkers in maternal blood and focuson the similarity between tumour invasion and embryogenesis as phenomena by c-MycBP and E?cadherin.This case control study included 50 women with RPL (25 primary RPL and 25 secondary RPL) from threeinfertility clinics in Iraq. In addition to 50 control women with no history of RPL and at least one childbirth. Both groups are matched in age and BMI. Blood sampling was done for all and protein level ofc-Myc BP and E-cadherin were measured by ELISA Kit and analysis done according to the manufacturerrecommendations. The result presented in this study showed a significant difference in c?MycBP level(p<0.001) and E?cadherin (p<0.001) between patients and control. A significant positive correlation hasbeen found between these two biochemical markers (p <0.001, r=?0.39). The present study showed thatdecreasing both c-MycBP and E-cad serum level signpost possible hypothesis that these proteins participatein one way or another in RPL pathogenesis which affect cell proliferation and invasion. However, thisbinding protein transcription factor is a part of a coordinated network of various set of partners whichneed further studies in future. Taken together, additional studies are required to understand and clarify theimportance of these biomarkers on this multifactorial condition.